MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN KONSEP BILANGAN SATU SAMPAI LIMA MELALUI PERMAINAN CONGKLAK BAGI ANAK TUNAGRAHITA SEDANG - Wahyu Dini Pangestu, Zulmiyetri, Yarmis Hasan (Universitas Negeri Padang, 2013)
The research was motivated by the problems of children being tunagrahita (x) is difficult to know the concept of numbers one to five in the DIV class in Manggis SDLB Ganting Bukittinggi. I like to have the ability of children to know the concept of numbers can be fulfilled through congklak game. This research uses experimental approach in the form of Single Subject Research (SSR). Assessment in this study, is to carry out tests deeds to the children, the extent to which children's ability to recognize numbers are mentioned beilangan, showing numbers, counting, and a pair of objects to numbers one to five. the ability of children at baseline conditions ranged from 13% -26%. Once in the intervention, using the game congklak children increased to 33% -86%, so the hypothesis can be accepted, so by using congklak games can be applied so that children can recognize the concept of numbers one through five for child mental retardation (x)